Pengaruh Model Think Pair Share (TPS) terhadap Kemampuan Menulis Teks Berita Siswa Kelas VII SMP PGRI 1 Palembang - Muhammad Erlangga; Missriani Missriani; Siti Rukiyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
News writing is a fact-based and actual writing activity based on actual events aimed at conveying information to the audience. Therefore, learning news writing material is poorly understood by students because there is still a lack of interactive students in learning and discussing. Based on this, the problem in this study is whether there is an effect of the think pair share model on the ability to write news of VII grade students of SMP PGRI 1 Palembang. The purpose of this research is to know and describe the effect of think pair share model on the ability to write news of seventh grade students of SMP PGRI 1 Palembang. The results showed that on the average value of the test results, where the class that used the think pair share learning model the average value of the students' news writing test results was x =81.23, while in the class that used the usual learning model (conventional) the average value of the news writing test results was x =62.65, from the analysis obtained thiutng, = 6.56 and ttabel = 4.03 with db = 48 the critical t price is located at alpha = 0.05, then the value of tcount> ttable = 6.56> 4.03, which means the application of the think pair share model has a significant positive effect on the ability to write news.